Traditional Chinese exercises for motor symptoms and mobility in patients with Parkinson's disease: a systematic review and meta-analysis - Yuan, Fumei; Wang, Hong (Frontiers in Aging Neuroscience, 2025)
ObjectiveTo systematically assess the impact of TCE on the efficacy of interventions targeting motor symptoms and mobility in people with Parkinson's disease.Methodsa computerized search was performed for randomized controlled trials assessing TCE intervention for motor symptoms and mobility in Parkinson's disease patients across PubMed, Web of Science, Embase, Cochrane Library, EBSCO, China National Knowledge Infrastructure (CNKI), WanFang data, and VIP database, covering the period from the inception of the databases to January 2025.Resultsfourteen publications encompassing 833 Parkinson's disease patients were incorporated into the literature. A meta-analysis indicated that TCE enhanced the UPDRS-III score (MD = −4.38, 95% CI [−5.95, −2.81]), TUGT score (MD = −2.78, 95% CI [−4.02, −1.54]), and BBS score (MD = 3.68, 95% CI [2.09, 5.27]). The effect size was compared with the Minimum Clinically Important Difference (MCID), and it was found that patients could perceive the alleviation of motor symptoms (UPDRS-III). Subgroup analyses indicated that for motor symptoms (UPDRS-III), the optimal exercise regimen was Qigong (MD = −5.54) with an exercise duration of <12 weeks (MD = −4.79), <3times/week (MD = −4.67), and each session duration ≥60 min (MD = −4.86). For functional walking ability (TUGT), the optimal exercise was Tai Chi (MD = −3.41) with an exercise duration of ≥12 weeks (MD = −3.81), exercise frequency <3times/week (MD = −3.04), and each session duration ≥60 min (MD = −3.05). For balance (BBS), the optimal exercise was also Tai Chi (MD = 5.03) with an exercise duration of ≥12 weeks (MD = 3.75), <3times/week (MD = 3.73) and session duration of ≥60 min (MD = 4.16).ConclusionThis meta-analysis indicates, the TCE intervention enhances motor symptoms and mobility in people with PD, with optimal outcomes observed from exercise frequency <3times/week, each session duration ≥60 min. The duration of the patient's disease and the intervention group type influenced the effect size (MD).